METHODOLOGY FOR REALIZING STUDENTS' INDIVIDUAL POTENTIAL THROUGH THE DEVELOPMENT OF CREATIVITY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The development of students' creative abilities and the full realization of their individual potential is a pressing issue in the modern education system. 21st-century society requires specialists who think innovatively and can offer non-traditional solutions. This article analyzes the psychological and pedagogical foundations for developing creativity in higher education, along with modern methodologies and approaches proposed based on scientific research. The article emphasizes an individual approach, detailing the stages of diagnosis, development, and assessment. Consequently, higher education institutions must abandon traditional methods and implement interdisciplinary and technologically integrated methodologies to prepare innovative individuals.